Incidence, risk factors and management practices in post-viral encephalitis epilepsy: A long-term, nationwide population-based study and review of literature - Cvetkovska, Emilija; Adjami, Bekim; Boshkovski, Bojan; Babunovska, Marija; Stevanovikj, Milena; Cvetanovska, Marija; Kuzmanovski, Igor; Punia, Vineet (Elsevier BV, 2026)
Objective: We investigated the incidence, risk factors, and management of post-viral encephalitis epilepsy (PEE) in a nationwide cohort in North Macedonia. Additionally, we conducted a comprehensive literature search on PEE. Methods: Data were obtained from the electronic National Health System (eNHS), encompassing all patients diagnosed with viral encephalitis (VE) in 2016. Patients with pre-existing epilepsy diagnoses were excluded. Clinical, neuroimaging, and EEG data were collected and analyzed, and participants were followed for seven years. Results: Of 1660,584 individuals registered in the eNHS in 2016, 68 were confirmed to have VE (incidence: 4.1/100,000). Among these, six patients died during hospitalization, and the remaining 62 were included in the study cohort. Acute symptomatic seizures (ASyS) occurred in 39 % of patients, with focal to bilateral tonic-clonic seizures (FBTCS) being the most common seizure type. Over the seven-year follow-up period, 11 patients (18 %) developed PEE, with 73 % of cases diagnosed within the first year. Significant risk factors for PEE included ASyS, younger age, and epileptiform abnormalities on EEG. By the end of the follow-up, seven patients with PEE (64 %) remained on antiseizure medications (ASMs). Conclusions: Our results confirm ASyS and highlight acute electro-clinical findings and young age as risk factors for PEE. There is a need for evidence-based clinical pathways and care protocols for patients at risk.
Keywords: Acute symptomatic seizures; Postencephalitic epilepsy